PENINGKATAN HASIL BELAJAR TEMA 8 MELALUI MODEL FLIPPED CLASSROOM BERBANTU MEDIA AUDIO VISUAL PADA PESERTA DIDIK KELAS 5 SDN 2 MAYONGLOR (JS (JURNAL SEKOLAH), 2021)
Abstract : Learning Outcomes of Theme 8 Through the Flipped Classroom Model Assisted by Audio Visual Media for Class 5 Students at SDN 2 Mayonglor.The background that drives this research is the learning outcomes of fifth grade students at SD Negeri 2 Mayonglor on the results of observing the learning completeness of grade 5 students at SDN 2 Mayonglor during the final assessment of semester I on science learning content there are 11 students or 52.3% of 21 5th grade students whose scores are still below the KKM value of 65. This study aims to determine the improvement of learning outcomes through the Flipped Classroom learning model Assisted by Audio Visual Media in 5th Grade Students of SDN 2 Mayonglor Academic Year 2020/2021. This article describes the results of classroom action research conducted at SDN 2 Mayonglor in semester 2 of the 2020/2021 Academic Year. The subject of this research is the learning outcomes of the fifth grade students of SD Negeri 2 Mayonglor, totaling 21 students consisting of 14 male students and 7 female students. Data collection tools used evaluation test sheets in the form of multiple choice questions, affective assessment sheets, psychomotor assessment sheets, and documentation. The results of the increase that occurs can be seen in each cycle. The results of this study indicate that the use of the Flipped Classroom learning model with the aid of audio-visual media can improve the learning outcomes of students in class V Theme 8 at SD Negeri 2 Mayonglor for the 2020/2021 academic year.Keywords: flipped classroom learning modelAbstrak Peningkatan Hasil Belajar Tema 8 Melalui Model Flipped Classroom Berbantu Media Audio Visual Pada Peserta Didik Kelas 5 SDN 2 Mayonglor.Latar belakang yang mendorong penelitian ini adalah hasil belajar peserta didik kelas V di SD Negeri 2 Mayonglor pada hasilobservasiketuntasanbelajarpesertadidikkelas5SDN2Mayonglor saat penilaian akhir semester I pada muatan pembelajaran IPAterdapat 11 peserta didik atau 52,3% dari21 peserta didik kelas 5yangnilainyamasih dibawah nilai KKM 65.Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar melalui model pembelajaran Flipped Classroom Berbantu MediaAudio VisualPada Peserta DidikKelas5 SDN2Mayonglor Tahun Pelajaran 2020/2021. Artikel ini memaparkan hasil penelitian tindakan kelas yang dilaksanakan di SDN 2 Mayonglor pada semester 2 Tahun Pelajaran 2020/2021.Subjek penelitian ini adalah hasil belajar peserta didik Kelas V SD Negeri 2 Mayonglor yang berjumlah 21 peserta didik yang terdiri dari 14 peserta didik laki “ laki dan 7 peserta didik perempuan.Alat pengumpulan data menggunakan lembar tes evaluasi dalam bentuk soal pilihan ganda, lembar penilaian afektif, lembar penilaian psikomotor, serta dokumentasi. Hasil peningkatan yang terjadi dapat dilihat pada setiap siklusnya. Hasil penelitian ini menunjukkan bahwa penggunaan model pembelajaran Flipped Classroom berbantu media audio visual dapat meningkatkan hasil belajar peserta didik kelas V Tema 8 di SD Negeri 2 Mayonglor Tahun Pelajaran 2020/2021.Kata Kunci: model pembelajaran flipped classroom